2019
DOI: 10.1002/cctc.201901243
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Oxygen Vacancies in the Synthesis of 1, 3‐Butadiene from Ethanol

Abstract: The t‐ZrO2 doped with Zn catalyst and t‐ZrO2 as reference were employed in the butadiene synthesis from ethanol. Both catalysts were characterized by NH3‐TPD, CO2‐TPD, TPSR, the MPV model reaction, ICP, BET and EPR. Adding 0.2 wt% Zn to t‐ZrO2, the selectivity to butadiene increases three fold whereas the one to ethylene decreases. When ZrO2 is doped, the number of basic sites increases and the number of acid sites decreases. The TPSR spectra indicate that the acetaldehyde generation is the rate limiting step … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 36 publications
3
29
0
4
Order By: Relevance
“…The addition of zinc oxide successfully suppressed ethanol dehydration-a phenomenon observed in many catalytic systems for the ethanol-tobutadiene reaction. 127,197,247 Still, the butadiene yield remained below 20%. Only with the addition of ZrO 2 could a yield of 52.5% be achieved, marked by a sharp consumption of acetaldehyde compared to other samples.…”
Section: Catalysis Science and Technologymentioning
confidence: 97%
See 1 more Smart Citation
“…The addition of zinc oxide successfully suppressed ethanol dehydration-a phenomenon observed in many catalytic systems for the ethanol-tobutadiene reaction. 127,197,247 Still, the butadiene yield remained below 20%. Only with the addition of ZrO 2 could a yield of 52.5% be achieved, marked by a sharp consumption of acetaldehyde compared to other samples.…”
Section: Catalysis Science and Technologymentioning
confidence: 97%
“…Recent findings concerning Znmodified ZrO 2 catalysts used in the Lebedev process lead to the same conclusion, that zinc-dopants also introduce oxygen vacancies, and that the latter act as the basic sites needed for acetaldehyde formation. 247 The addition of ZnO or hemimorphite has also been shown to introduce new Lewis acid sites in catalysts. 109,125,227,230,248 Some authors have attributed the higher selectivity towards dehydration products compared to Ag or Cu to these acid properties.…”
Section: Dehydrogenation Promotersmentioning
confidence: 99%
“…Zn 2+ ) induces the formation of oxygen vacancies (V O ) and, as a direct consequence, generates defects featured by coordinatively unsaturated Zr 4+ sites (cus-Zr 4+ ) which can act as strong basic and acid sites respectively. 34 Carbon mono-and di-oxide activation was reported to be facilitated by the presence of neighbouring cus-Zr 4+ ion sites and V O . 25,[35][36][37] Thus, V O enhance the Brønsted acidity of Zr-OH groups adjacent to cus-Zr 4+ cations.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of acidic ZrO 2 /SiO 2 and basic MgO/SiO 2 catalysts suggested that the strong basic sites in MgO/SiO 2 are more reactive in condensation reactions but suffer fast deactivation, in contrast to the acidic sites of both ZrO 2 /SiO 2 and MgO/SiO 2 . [81] Table 3 summarizes recent ETB acidic catalytic systems with SiO 2 [82][83][84][85][86][87][88][89][90][91][92][93] and ZrO 2 [94][95][96] as support. Some of these systems are used for the ethanol/acetaldehyde to butadiene conversion (step 2 of the two-step process).…”
Section: Acidic Catalytic Systemsmentioning
confidence: 99%
“…Chagas et al added 0.2 wt% Zn to tetragonal ZrO 2 which increased the number of basic sites whereas the number of acid sites decreased. [93] The substitution of Zn 2 + for Zr 4 + in ZrO 2 forms oxygen vacancies as well as coordinatively unsaturated (cus) Zr 4 + ions. The oxygen vacancies are strong Brønsted basic sites while cus Zr 4 + are Lewis acid sites.…”
Section: Acidic Catalytic Systemsmentioning
confidence: 99%